First Aid Treatments of Some Common Problems and Diseases - Chouhan, Ankit (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT First Aid is the temporary help given to an injured or a sick person before professional medical treatment can be provided. This timely assistance, comprising of simple medical techniques, is most critical to the victims and is, often, life saving. Some common problems, illness, injury or diseases require the first aid treatment at the acute attack or at uncontrollable condition for that person. Any layperson can be trained to administer first aid, which can be carried out using minimal equipments. Certain self-limiting illnesses or minor injuries may not require further medical care past the first aid intervention. It generally consists of a series of simple and in some cases, potentially life-saving techniques that an individual can be trained to perform. The key aim of first aid for common problems is to preserve life, prevent further harm, and to promote recovery of that person. Key words: First aid, common treatments, common diseases